Optimizing clean water filtration through the application of science and technology: Reverse osmosis method - Yuliati; Alfina Baharuddin; Hardi; Siti Astachya Ananda Sofyan; Suharni A. Fachrin; Ella Andayanie (LPPM Politeknik Sandi Karsa, 2025)
Water is the fundamental basis for all biological and human activities. Water is believed to be a natural resource that will never run out and will always be available. Nonetheless, the availability of water as a natural resource is restrained due to its relatively constant hydrological cycle, thus making it limited in supply. The methods used during the activity were lectures and discussions. At the beginning of the activity, the team conducted counseling related to well water sanitation, its impact, and how to overcome it. The method of this counseling stage is carried out through 5 stages, namely: socialization stage and the implementation stage. This activity includes 3 sessions, among others: First stage: Pre-test, which is given through a questionnaire, lecture, question and answer, and discussion methods. Posttest and assessing the results of the posttest, the technology application stage, the monitoring and evaluation stage, and the program sustainability stage. The results of the service activities showed that the educational program on access to clean water, sanitation, and the effects of borehole water for health significantly increased the knowledge of the participants. The average score increased from 19.22 in the pre-test to 21.18 in the posttest, with a p-value of 0.001, indicating a significant difference. This result confirms the effectiveness of the clean water and sanitation education program